Protecting White Victimhood and Technologies of Whiteness Through “Trauma-Informed” School Social Work - Mayor, Christine (Critical Education, 2025)
Few studies have explored how whiteness might be reinforced in the “trauma-informed” assessments, practices, and policies of school social workers. This critical qualitative research study asks: How does whiteness structure how Canadian school social workers recognize, understand, and respond to students’ expressions of trauma in K-12 schools? Data were collected from nineteen school social workers in Ontario using vignettes and semi-structured interview questions. Data were analyzed through critical thematic analysis, guided by critical trauma and critical whiteness theories. Findings include school social workers protecting white victimhood and the embedding of (neoliberal) technologies of whiteness into trauma-informed practices. Additionally, participants demonstrated using “wise practices” to resist these pressures and meet the needs of racialized students. Recommendations include the adoption of different trauma assessment tools; alternative training of social workers; policy advocacy; and future areas for research.